At the Interface between Sociolinguistic and Grammatical Development: The Expression of Futurity in L2 French: A Preliminary Study - Howard, Martin (Arborescences)

(untitled) (Département d'études françaises, Université de Toronto, 2015)
As an example of socio-grammatical variation in target language French, the morphological variation at work in the expression of futurity constitutes an interesting area to intricately relate the L2 learner’s sociolinguistic and grammatical development. This conceptual entity is all the more interesting since previous studies of this variable in native speaker French point to a certain discrepancy between prescriptive and sociolinguistic norms in the speaker’s choice between the inflected and periphrastic forms as well as in the use of the present to mark futurity, whereby the prescriptively hypothesized semantic restrictions on the use of each form are not seen to be upheld in real language usage. This paper is concerned with the acquisition challenge that such a threefold choice poses to the L2 learner of French, based on a quantitative cross-sectional analysis of Irish instructed and study abroad learners of French. Reflecting previous studies of other variables (see, for example, Dewaele 2004; Mougeon et al. 2010), results suggest an important effect for naturalistic exposure on the acquisition of native speaker norms surrounding the expression of futurity, as well as for the actual target language variety to which the learners are exposed.